Inheritance of yellow colour in safflower (Carthamus tinctorius L.) - T. V. Leus (Вавиловский журнал генетики и селекции)
Safflower is a minor crop, and its genetics is poorly known. Four types of safflower corolla color are recognized: red, orange, yellow, and white. As the information on color inheritance is incomplete and contradictory, we aimed to study the inheritance of yellow color in safflower. The research conducted in 2009–2013 involved 11 accessions with red, orange, yellow, and white corollae. Samples were obtained by self-pollination for several years. Their progenies by open and controlled pollination were genetically analyzed. Two emasculation techniques were used in artificial pollination: the Indian mass-emasculation technique with polythene bags and the washout pollen technique we’ve elaborated. The results were evaluated by the Chi-square test. They revealed several types of yellow color inheritance. Crosses of a yellow-corolla plant to a plant with another corolla color yielded yellow-corolla F1 progenies. Segregation of F2 produced all the four colors, the yellow color being the most abundant. However, when the parental plants had corolla colors other than yellow in some cases F2 contained fewer yellow-corolla plants, while other corolla colors were predominant. The dominant gene determining the yellow color is proposed to be designated as C for Chrome. The recessive allele of this gene permits the development of other corolla colors.